Rice Stomatal Mega-Papillae Restrict Water Loss and Pathogen Entry - Pitaloka, Mutiara K.; Harrison, Emily L.; Hepworth, Christopher; Wanchana, Samart; Toojinda, Theerayut; Phetluan, Watchara; Brench, Robert A.; Narawatthana, Supatthra; Vanavichit, Apichart; Gray, Julie E.; Caine, Robert S.; Arikit, Siwaret (Frontiers in Plant Science, 2021)
Rice (Oryza sativa) is a water-intensive crop, and like other plants uses stomata to balance CO2 uptake with water-loss. To identify agronomic traits related to rice stomatal complexes, an anatomical screen of 64 Thai and 100 global rice cultivars was undertaken. Epidermal outgrowths called papillae were identified on the stomatal subsidiary cells of all cultivars. These were also detected on eight other species of the Oryza genus but not on the stomata of any other plant species we surveyed. Our rice screen identified two cultivars that had ‘mega-papillae’ that were so large or abundant that their stomatal pores were partially occluded; Kalubala Vee had extra-large papillae, and Dharia had approximately twice the normal number of papillae. These were most accentuated on the flag leaves, but mega-papillae were also detectable on earlier forming leaves. Energy dispersive X-Ray spectrometry revealed that silicon is the major component of stomatal papillae. We studied the potential function(s) of mega-papillae by assessing gas exchange and pathogen infection rates. Under saturating light conditions, mega-papillae bearing cultivars had reduced stomatal conductance and their stomata were slower to close and re-open, but photosynthetic assimilation was not significantly affected. Assessment of an F3 hybrid population treated with Xanthomonas oryzae pv. oryzicola indicated that subsidiary cell mega-papillae may aid in preventing bacterial leaf streak infection. Our results highlight stomatal mega-papillae as a novel rice trait that influences gas exchange, stomatal dynamics, and defence against stomatal pathogens which we propose could benefit the performance of future rice crops.